PENGENDALIAN KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA MASA KEHAMILAN DI WILAYAH KERJA PUSKESMAS RAMBAH - Nana Aldriana (Maternity and Neonatal : Jurnal Kebidanan, 2021)
Chronic Energy Deficiency (KEK) is defined as a condition in which women experience chronic food shortages (Chronic). KEK is diagnosed if there is an upper arm circumference (LILA) <23.5 cm. There are many determinants or factors that cause SEZs, including lack of knowledge, income, age, and parity. Pregnancy with KEK is usually accompanied by anemia which facilitates complications such as bleeding and the birth of a baby with LBW. The purpose of this study was to determine the determinants of chronic energy deficiency during pregnancy in the Rambah Public Health Center. The research method is quantitative analytic with cross sectional design. The population in this study were 30 trimester pregnant women in the Rambah Public Health Center. The sample technique used was total sampling. Data were analyzed by univariate and bivariate (chi square test). The results showed that 16% of pregnant women in the third trimester with KEK. From the results of the bivariate test, there was a relationship between knowledge and the incidence of KEK (p-value = 0.003), there was no significant relationship between age (p-value = 0.589), parity (p-value = 1,000), and income (p-value = 0.068 ), with the incidence of KEK during pregnancy. The conclusion in this study is that the knowledge factor is related to the incidence of KEK. Factors of age, parity, and income are not related to the incidence of KEK. Based on the research results, it is deemed necessary to provide knowledge to prospective pregnant women and pregnant women about the importance of maintaining good nutrition so that a healthy pregnancy takes place.